Dampak Kondisi Pandemi di Indonesia Terhadap Trend Penjualan (Studi Kasus pada PD. Sumber Jaya Aluminium) - Lingga Yuliana (JRB-Jurnal Riset Bisnis, 2020)
The purpose of this study was to analyze the sales conditions at PD. Sumber Jaya Alunimium, through the sales data pattern, identified the relationship between PSBB and the sales impact of PD. Sumber Jaya Aluminum, as well as factors from the decline in sales due to the Pandemic conditions. The research method used is descriptive quantitative analysis through purposive sampling technique with Analytic Network Process (ANP). The results showed that the sales data pattern of PD. Sumber Jaya Aluminum during the period December 2019 to April 2020 has a sales trend that tends to decline. Based on processing with the Analytic Network Process (ANP), Large-Scale Social Restrictions (PSBB) are a problem with the decline in company sales which causes the company's operations to stop. This is followed by the unavailability of raw materials, decreased demand and the effect of panic buying.